Transmission of Global Food Prices to Domestic Prices in Developing Countries : Why It Matters, How It Works, and Why It Should Be Enhanced - World Bank (Washington, DC, 2017)
Transmission of international food prices to domestic prices is essential to pursue comparative-advantage-based, sustainable agricultural production, and to ensure domestic production responds to global food scarcity or surplus. (i) International prices are opportunity costs for most price-taking developing countries and are crucial in determining an efficient distribution of domestic resources. When the long-term trend of international prices is transmitted slowly and imperfectly to domestic markets, consumers and producers make decisions based on prices that do not represent their real social costs and benefits. There is strong empirical evidence from both developing and developed countries that any large, sustained deviation of domestic prices from world prices in either direction leads to substantially sub-optimal outcomes and slows the rate of economic growth; and (ii) as international food prices reflect global scarcity or surplus, their transmission to domestic prices can help improved the global responsiveness of the food system to shocks. The recent increase in the volatility of international food prices is, therefore, a big concern. These volatile and unpredictable prices may undermine incentives for farmers to respond to high price levels with the critical increase in production needed to bring food prices down. In practical terms, farmers decide what to plant and countries deciding when to import face uncertainty in the likely distribution of world food prices and greater consequences when using past price levels and distributions to guide current decisions. This uncertainty keeps food prices high for a longer period, leading to fundamental food security risks for consumers and governments. To achieve more efficient domestic price formation, policy actions need to focus on (i) strengthening the integration of local markets with international markets (through investments in infrastructure and market-oriented policies), especially local markets that are more volatile than international markets, (ii) reducing global food price volatility, including through more discipline on trade policy, and (iii) strengthening safety nets to rapidly and cost-effectively protect the poor and vulnerable from the food price spikes.